The concept of retributive and restorative justice in Islamic criminal law with reference to the Malaysian Syariah court - Wan Muhammad, Ramizah; Abdul Salam, Khairunnasriah (Syrahwa Publications, 2018)
Among the objectives of the punishments in Islamic criminal law as enunciated by the Muslim jurist are retributive, deterrence and reformation. Reformation is not only confined to reform the behaviour of the offender but also to reform the relationship between the offender and the victims as well as with the society. Due to the reason, restorative justice plays its role. In another perspective, the Islamic criminal punishment as set out in the Quran and Sunnah such as amputation of limbs, stoning to death and death penalty were criticized on the ground of their severity. However, in fact; the brighter side and wisdom of the punishments are less highlighted to the society such as forgiving, patience, reconciliation and opt for an alternative punishments for the purpose of amicable settlement between the victims and offenders rather than invoking physical punishment to the offenders. This paper seeks to highlight the concept and objectives of punishments in Islamic criminal law which specifically focuses on the retributive and restorative justice. Hence, it discusses the concept of restorative justice in Islamic criminal law within the purview of the Quran and Sunnah. As comparative reference, this paper examines the law and practice of punishment in Malaysian Shariah Court in order to see the extent of the application of retributive and restorative justice within Islamic criminal justice in Malaysia. This paper finds that the concept of restorative justice is not widely applied in the Malaysian Shariah Court in punishing the offender who is found guilty with Islamic criminal offence. It is concluded that the importance of the awareness on the importance and objectives of restorative justice need to be enhanced among the Islamic law practitioners and Islamic judiciary officers in Malaysian Syariah Court in to reform the offender.